FAKTOR-FAKTOR YANG MEMENGARUHI MANAJEMEN LABA DALAM INDUSTRI MANUFAKTUR - Dessya Christilla; Merry Susanti (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
Some companies tend for using earnings management to decorate their financial statements, this will make the financial statements do not look as they should. The goal of this study is to research the effect of profitability, leverage, firm size, and institutional ownership on earnings management of manufacturing companies listed in IDX between 2017 and 2020. Purposive sampling was used to obtain the samples, which results in a total of 260 companies. Panel data regression model was used as the data model, and the data is processed using Eviews version 12. The results shows that profitability and leverage have a significantly positive effect on earnings management, whereas firm size has a significantly negative effect on earnings management, and institutional ownership has a positive but insignificant effect on earnings management.